A Case of Special Complication following a Large Amount of Polyacrylamide Hydrogel Injected into the Epicranial Aponeurosis: Leukocytopenia. (20th October 2015) - Rong, Li; Lan, Shi-Jie; Shao, Ying; Chen, Zhe; Zhang, Duo
Abstract : Polyacrylamide hydrogel (PAAG) has been used as an injectable filler for soft tissue augmentation of different body parts, such as the face, breasts, and penis. However, this is the first report of leukocytopenia after injection of a large amount of PAAG in the epicranial aponeurosis. After receiving PAAG injection for craniofacial contouring, the female patient described herein experienced recurrent swelling, temporal pain (particularly with changes in ambient temperature and facial expression), and ultimately leukocytopenia due to widespread migration of the injected PAAG. We removed most of the PAAG from the affected tissues and the leukocytopenia disappeared 1 year after the operation. Based on this case, we hypothesize that injection of a large amount of PAAG into tissues that have ample blood supply, such as the epicranial aponeurosis, may induce leukocytopenia.